1981
DOI: 10.1080/03014468100004841
|View full text |Cite
|
Sign up to set email alerts
|

Climate and anthropometric variations in Europe and the Mediterranean area

Abstract: Fourteen anthropometric measurements collected among 85 European, North African and Middle Eastern populations have been studied with respect to eight climatic variables through zero-order correlations and multiple stepwise regressions. The average contribution of climate to the total variance of physical features between populations is 35%. The most important correlations of postcranial body measurements and nasal index are with the extremes of heat and dryness, while the head measurements are more sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
76
2
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 6 publications
(3 reference statements)
5
76
2
3
Order By: Relevance
“…For example, genetics (Abbie, 1947), environmental factors (Abbie, 1947;Beals et al, 1983), protein in the diet (Miller, 1970), psychological and physiological stress (Miller, 1970), medical facilities and care (Miller, 1970), natural climate (Crognier, 1981;Beals et al, 1983;Bharati et al, 2001). Other hypotheses about the factors that are potentially related to head form include heterosis (Billy, 1975), socioeconomic status (Schwidetzky, 1973;Pälsson and Schwidetzky, 1973;Miki, 1990) and nutrition or diet (Lasker, 1946).…”
Section: Discussionmentioning
confidence: 99%
“…For example, genetics (Abbie, 1947), environmental factors (Abbie, 1947;Beals et al, 1983), protein in the diet (Miller, 1970), psychological and physiological stress (Miller, 1970), medical facilities and care (Miller, 1970), natural climate (Crognier, 1981;Beals et al, 1983;Bharati et al, 2001). Other hypotheses about the factors that are potentially related to head form include heterosis (Billy, 1975), socioeconomic status (Schwidetzky, 1973;Pälsson and Schwidetzky, 1973;Miki, 1990) and nutrition or diet (Lasker, 1946).…”
Section: Discussionmentioning
confidence: 99%
“…57,60,61 Unsurprisingly, these patterns extend beyond shape to body composition, with 244 lean mass relative to height scaling inversely in association with annual temperature. 245 246 Low levels of lean/muscle mass have been linked with elevated susceptibility of populations 247 such as South Asian and Australian aboriginals to insulin resistance in obesogenic 248 settings, 19,20 and this scenario may apply to other populations with similar characteristics.…”
mentioning
confidence: 99%
“…Many hypotheses have been proposed for the secular changes in head form, such as environmental factors (Abbie, 1947), increased protein in the diet (Miller, 1970), decreased psychological and physiological stress (Miller, 1970), and increased medical facilities and care (Miller, 1970). Some investigators (Beals, 1972;Crognier, 1981;Beals et al, 1983;Bharati et al, 2001) have suggested that the occupation of cold climates was one of the circumstances that may have led to the increasing frequency of brachycephalic head form over time. Other researchers (Bielicki and Welon, 1964;Henneberg, 1976) believe that the brachycephalic head form have been selected as a consequence of evolutionary forces.…”
Section: Discussionmentioning
confidence: 99%